Identify the tests to measure physical characteristics and basic skills for the football players in Iraq - Mohammed, Mothna; Soh, Kim Geok; Tengku Kamaldem, Tengku Fadilah; Naji, Farah Layth (Australian International Academic Centre, 2016)
Background: Basic skills specification and physical characteristics are the most significant factors for Football players. Objective: This research aims to determine the most relevant tests to examine the basic skills and physical characteristics for the football coaches in Karbala. Methods: The participants of this study includes 92 Football player (body weight 68±16 kg (mean±SD), height 172.5±17.5 cm, age 21±3 year ) who were chosen from the 4 clubs in Karbala, Iraq. Methods: To choose the appropriate tests for basic skills and physical characteristics the opinion of the experts was used followed by 2 questionnaires, scored from 1 to 5. The tests were recommended for this study and the questionnaire consisted of seven items. The researcher adapted the questionnaires from previous studies. Results: The findings of questionnaires revealed that vertical jump and dribbling 25 m, sit down and stand up, Nelson reaction, 30 m sprint, passing with wall and Shuttle test are chosen to test the Physical characteristics in football, whereas, accuracy test for shooting, heading the ball, competitor evasion, receiving ball, zigzag dribbling and passing accuracy are chosen to test basic skills in football. Conclusion: The tests which were chosen in this study can be adopted by coaches as a practical way in Karbala and other regions in Iraq and also in other countries. The experts can use the findings of these tests and compare professional athletes and other football players.